Female Empowerment Redefinition in The Devil Wears Prada: A Character Analysis of Miranda and Andrea - Cakrawati, Titis Dewi; Aisyiyah, Muhsiyana Nurul; Sandy, Fadillah (IAIN Syekh Nurjati Cirebon, 2024)
Deconstruction plays a significant role in literary analysis as a method of approaching distinct works by querying their original objectives. The Devil Wears Prada is a 2006 film that was adapted from Lauren Weisberger's 2003 book of the same name. The protagonist, Andrea Sachs, a 20-something woman, is following her dream of becoming a journalist by working as Miranda Priestly's assistant. This study aimed to describe the deconstruction of female empowerment on the two main characters of the movie The Devil Wears Prada, namely Miranda Priestly and Andrea Sachs. It was qualitative research with a critical discourse analysis approach. The researchers examined the movie and the screenplay to find elements supporting the female empowerment deconstruction in the two characters. The findings of this study elaborated the deconstruction of female empowerment in Miranda’s character and in Andrea’s character. The deconstruction of female empowerment in Miranda’s character shows that Miranda does not represent the idea of female empowerment. With her material and professional success, she seems to represent the notion but in a conventional way. Meanwhile, female empowerment is challenged with the Derrida’s theory and redefined through Andrea’s character. Andrea established herself as an empowered woman who shows integrity and makes unconventional significant decisions in her life. She also can take control and empower other people in the working place by showing sympathy to her colleagues including Miranda when her career was threatened.